2020
DOI: 10.31557/apjcp.2020.21.8.2343
|View full text |Cite
|
Sign up to set email alerts
|

Progression Free Survival and Predictor of Recurrence in DLBCL patients with Negative Interim 18FDG PET/CT Using Standardized Imaging and Reporting Protocols

Abstract: Background: To determine progression free survival (PFS) and predictor of recurrence in patients with diffuse large B-cell lymphoma (DLBCL) with negative interim 18 FDG PET/CT (iPET) using standardized imaging and reporting protocols. Materials and Methods: This prospective study was conducted at PET/CT Section of a JCIA accredited healthcare facility from December 2015 till February 2020. Patients with DLBCL having complete metabolic response (CMR; Deauville score: 1-3) on iPET were selected and followed for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…A mean effective dose of 0.013 mSv/MBq was measured, which is similar to the routinely used glucose analogue [ 18 F]FDG [ 13 , 14 ]. However, new generations of PET/CT imaging scanners and recent efforts have indicated that a lower [ 18 F]FDG dose is preferable [ 15 , 16 ], and thus the [ 18 F]Me4FDG dose can likely be reduced as well. Moreover, from the findings of the study, it is clear that [ 18 F]Me4FDG was very well tolerated by the volunteers, as we did not detect any significant changes in the measured vital and laboratory parameters before and one hour after the intravenous injection of this tracer.…”
Section: Discussionmentioning
confidence: 99%
“…A mean effective dose of 0.013 mSv/MBq was measured, which is similar to the routinely used glucose analogue [ 18 F]FDG [ 13 , 14 ]. However, new generations of PET/CT imaging scanners and recent efforts have indicated that a lower [ 18 F]FDG dose is preferable [ 15 , 16 ], and thus the [ 18 F]Me4FDG dose can likely be reduced as well. Moreover, from the findings of the study, it is clear that [ 18 F]Me4FDG was very well tolerated by the volunteers, as we did not detect any significant changes in the measured vital and laboratory parameters before and one hour after the intravenous injection of this tracer.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, some urea-based PSMA ligands have been developed. These molecules display favorable binding affinity and stability with very efficient internalization into the cells [46][47][48] . The first urea-based compound to target PSMA in the brain was designed by Kozikowski et al 49 .…”
Section: Radiolabeled Psmamentioning
confidence: 99%
“…Advanced image reconstruction methods 13–15 and improved detectors have contributed to PET/CT images of much higher spatial resolution and signal‐to‐noise ratio even at substantially lower injected radiotracer dosages. In addition, new CT hardware and software has been proposed to minimize radiation exposure due to the CT component 1,16–18 …”
Section: Introductionmentioning
confidence: 99%
“…In addition, new CT hardware and software has been proposed to minimize radiation exposure due to the CT component. 1,[16][17][18] Previous studies reported that CT contributes to over 50% of the estimated average radiation exposure in 18 F-fluorodeoxyglucose ([ 18 F]FDG) PET/CT examinations-depending on the application. 16,17,19 In South Korea, a nationwide survey was conducted involving all institutions operating PET/CT scanners to evaluate the patient's effective dose for different diagnostic PET/CT procedures performed with various PET tracers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation